Analisis Penggunaan Bahasa Indonesia dalam Media Sosial Implementasi di Marketing STIE Ganesha - Abdul Kohar; Adi Wicaksono; Farhat Abas; Muhammad, Muhammad; Faroida Awalia (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
The Indonesian language plays a strategic role as a national identity and an effective communication tool capable of reaching various segments of society. In the digital era, social media serves as a primary platform for disseminating information and promoting institutions, including higher education institutions. As a competitive institution, STIE Ganesha requires an effective Indonesian-language-based marketing strategy to attract prospective students, maintain a positive institutional image, and enhance its competitiveness amidst intense digital competition. This research is crucial as the mastery and application of the Indonesian language within a digital context significantly influence communication success, especially in reaching a diverse audience. Language misuse can lead to misunderstandings, reduce credibility, and weaken the impact of marketing messages. This study aims to analyze the patterns of Indonesian language use in STIE Ganesha's social media content, identify the strengths and weaknesses in delivering marketing messages, and propose language use strategies that are both grammatically correct and suitable for social media audiences. The expected outcomes include: (1) scientific publication in a SINTA 4-accredited journal, namely the Indonesian Journal of Multidisciplinary Research (IJOMR), Volume 5 Number 1, March 2025; (2) a practical guide for STIE Ganesha's marketing team in optimizing digital communication; and (3) enhancement of institutional image through more professional and engaging social media content.